Gluttony : The seven deadly sins - Prose, Francine, 1947-; New York Public Library (Oxford : Oxford University Press, 2003)
"Here, novelist and critic Francine Prose serves up a marvelous banquet of witty and engaging observations on the most delicious of deadly sins. Prose traces how our negative notions of gluttony have evolved along with our ideas about salvation and damnation, health and illness, life and death. At the same time, Prose reminds us that it is also an affirmation of pleasure and passion. "The broad, shiny face of the glutton," Prose writes, "has been and continues to be the mirror in which we see ourselves, our hopes and fears, our darkest dreams and deepest desires." Never have we delved more deeply into this mirror than in this insightful and stimulating book. Book jacket."--BOOK JACKET.
Chapter 1. Is Gluttony a Sin? -- Chapter 2. The Wages of Sin -- Chapter 3. The Real Wages of Sin -- Chapter 4. Great Moments in Gluttony.
Originally published: 2003.
Includes bibliographical references and index.
Keywords: Gluttony -- Religious aspects -- Christianity; Gluttony